HUMANIZATION CONCEPT OF HIGHER EDUCATION AS A MEANS OF PERSONAL DEVELOPMENT REALISATION OF FUTURE MANAGERS OF TOURISM - Чорна, M. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The essence of concept «humanization of higher education» is defined and its influence on the professional development of future tourism experts is determined